1992
DOI: 10.1080/02681219280000391
|View full text |Cite
|
Sign up to set email alerts
|

Microsporum gypseumcomplex in man and animals

Abstract: Twenty-eight strains of the Microsporum gypseum complex isolated from humans and animals were studied. The perfect form was found for 25 of the isolates. Nannizzia incurvata was the species most frequently involved in human pathology, while Nannizzia gypsea was most frequently found on animal lesions. Nannizzia fulva was rarely involved pathologically and Nannizzia corniculata was not isolated during this study. It is surprising to note that this species was not found even though most of our strains (22/28) ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 6 publications
1
12
0
1
Order By: Relevance
“…16 The keratinophilic fungi such as M. gypseum and M. cookei isolated in this study have been reported to cause infection in human. 17,18 With the continuing increase in the number of severely immunocompromised patients, hospitals are faced with the growing problem of opportunistic fungal infections. As treatment of these infections is difficult, and the outcome often fatal, preventive measures are of major importance in the control of invasive fungal infections, therefore, full understanding of their epidemiology is crucial in the development of effective preventive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…16 The keratinophilic fungi such as M. gypseum and M. cookei isolated in this study have been reported to cause infection in human. 17,18 With the continuing increase in the number of severely immunocompromised patients, hospitals are faced with the growing problem of opportunistic fungal infections. As treatment of these infections is difficult, and the outcome often fatal, preventive measures are of major importance in the control of invasive fungal infections, therefore, full understanding of their epidemiology is crucial in the development of effective preventive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…M. gypseum and M. fulvum are closely related organisms, and rich garden soils are their favorite habitats 3 . The M. gypseum ‐complex is implicated in cases of tinea capitis (rarely tinea favosa) and tinea corporis, and infection often results from direct contact with either soil or domestic pets; the fungus has been recovered from fur 1 , 4–6 . The prevalence rates are low when compared with other dermatophyte isolates, ranging from 0.72% to 5.2% 6–8…”
Section: Discussionmentioning
confidence: 99%
“…All the strains of M. gypseum were subjected to mating experiments [1]. The organisms were maintained on Takashio medium.…”
Section: Methodsmentioning
confidence: 99%
“…Microsporum gypseum is a geophilic dermatophyte widely distributed in soil throughout the world [1]. The discovery of the perfect state of this fungus in 1963 [2] revealed that M. gypseum in its teleomorphic state is a complex made up of three species.…”
Section: Introductionmentioning
confidence: 99%